Pengembangan Apartemen Cherax quadricarinatus Menuju Industri Akuakultur 4.0 - Nyimas Dalilati Razanah; Gracia Eirene Girsang; Juliana Pangaribuan; Monicha Enzelx Manulang; Natalia Natalia; Retno Cahya Mukti (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Razanah ND, Girsang GE, Pangaribuan J, Manullang ME, Natalia N, Mukti RC. 2020. Cherax quadricarinatus apartement development towards the aquaculture industry 4.0. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Red Claw (Cherax quadricarinatus) culture has problems, namely the narrower land for cultivation and controlling water quality. This study aims to develop Red Claw cultivation through an apartment system in a small area, to facilitate water quality control and increase the production of Red Claw. The writing method in this study uses the literature study method. The results of the study explain the comparison between the production of Red Claw using an apartment system and the cultivation of Red Claw using pond or aquarium. To produce as many as 20 Red Claw requires a pond with a size of 2m × 1m × 1m, while lobster cultivation using an apartment system only requires land measuring 1.5m × 0.17m × 0.79m. In addition, the cultivation of Red Claw with an apartment system can improve water quality for the better because it uses the RAS (Recirculating Aquaculture System) system, which is the use of water repeatedly through several stages of filtration to break down ammonia. So that the study of Red Claw cultivation through this apartment system can be used as a solution to developing and increasing the production and production of Red Claw.